Effects of gender and psychiatric comorbidity on the age of illness onset and the outcome of psychotic depression-A birth cohort study - Nietola Miika; Nordström Tanja; Miettunen Jouko; Korkeila Jyrki; Jääskeläinen Erika (Elsevier, 2025)
Background: Psychotic depression (PD) is an under-researched disorder with severe symptoms and course of illness. Little is known about gender differences relating to this condition and possible variation of prognosis based on comorbid pathology. Our aim was to analyze the effects of gender and psychiatric comorbidities on the age of illness onset and on the outcome of psychotic depression.
Methods: The study was carried out in the Northern Finland Birth Cohort 1966. We utilized register data to acquire information about lifetime psychiatric diagnoses, hospitalization, age of illness onset, rate of disability pensions and mortality. The PD group (n = 58) was defined based on a lifetime register diagnosis. We compared outcome variables in sub-groups based on gender and comorbid alcohol use or personality disorder.
Results: The prevalence of comorbid personality disorders was 38% (22/58) and comorbid alcohol use disorders 41% (24/58). PD patients with a personality disorder diagnosis had an earlier onset age (p<0.01) and a higher mortality rate (p = 0.03). Male gender (p = 0.03), comorbid alcohol use disorder (p<0.01) and personality disorder (p < 0.01) were all associated with more psychiatric hospitalization. Comorbid alcohol use disorder was more common among men (males: 61%; females: 29%; p = 0.03).
Limitations: National registers were the main source of diagnostic information.
Conclusions: Gender and psychiatric comorbidity have significant implications for the course of illness in PD in naturalistic settings, which is an important message for all clinicians. More research into the heterogeneity of PD is needed in order to guide research and clinical practice.